Monitoramento da corrosão de aços inoxidáveis imersos em fluidos da produção de biodisel - Layane Isabelli da Silva (2015)
The world's dependence of fossil fuels as well as the environmental damage caused by their burning drive the search for new, renewable and less polluting energy sources. One idea to decrease those effects has gained prominence. In this scenario, biodiesel comes forward as a feasible alternative to petroleum diesel. Believing in the biodiesel potential, Petrobras invested on implementation of biodiesel plants, in which corrosion plays a fundamental role in the used materials degradation. With this perspective, this research evaluates the corrosion resistance of 304L, 316L, 317L and 904L austenitic stainless steels, in acidified glycerin and reactive biodiesel media, from a biodiesel production plant. The corrosion evaluation was carry out by immersion tests with heating and constant stirring, in order to reproduce the plant process conditions, and also by the use of the electrochemical impedance spectroscopy technique (EIS) for monitoring steel corrosion during the immersion test time. The characterization of stainless steels was performed using scanning electron microscopy (SEM), atomic force microscopy (AFM) and energy dispersive spectroscopy (EDS). The results interpretation suggests that acid glycerin is more corrosive than reactive biodiesel and that 316L and 904L austenitic stainless steels are the most resistive to corrosion in both media